A summative evaluation of the human resource management program of the Indonesian Cooperative Management Institute (IKOPIN) - Sitompul, Anwar (Animo Repository, 2002)
This study was aimed at making a summative evaluation of the Human Resource Management Program of the Indonesian Cooperative Management Institute (IKOPIN) based on Stufflebeam's context - input - process - product evaluation model. The respondents consisted of the President of IKOPIN, the Dean, 3 administrators (Vice Dean 1, Secretary, and Head Administrarion Department), 3 employers, a random sample of 10 faculty members, 220 students, and 317 alumni who graduated from IKOPIN during the ten year period, 1989 to 1999. The study was conducted in school year 2000-2001 in IKOPIN, West Java Indonesia. Questionnaires and interview guides were used for data gathering purposes. Data were subjected to quantitative and qualitative analyses. Finding of the study are as follows: Context Evaluation. The vision-mission of IKOPIN is to be a center of excellence in the development of cooperative and medium, small enterprises with a three-fold function: education, research, and public service. It aims to produce graduates who are loyal to one God, and endowed with integrity, professionalism, and discipline, who will become innovative, productive experts in human resource management. Input Evaluation. The students were relativity young (20-21 years old) and generally belonged to low-income families. The course lecturers were not specialist, whose field s of expertise were in economics and agriculture. Facilities and library holdings for HRM were very limited. Process Evaluation. Problems in implementing the program included low salaries of lecturers and graduates who were generally employed in non-cooperative and non-entrepreneurship work. In addition, IKOPIN did not have information about industry requirements for human resource management graduates. Product Evaluation. Most of the alumni were not able to practice their HRM training. Based on the results of the context, input, process, and product evaluation, these is an urgent need to improve the HRM courses to better quality the graduates for human resource management position. Furthermore, IKOPIN should be more selective in employing lecturers, improve HRM facilities and library holdings, and continuously update the HRM program based on job market requirements.